INFLUENCE OF BAIT ATTRACTORS ON CATCH YIELD OF BOAT LIFT NETS IN JAKARTA BAY WATERS - Ariyanto; Yusrizal; Sudrajat, Danu (Departemen PSP IPB, 2025)
The use of light attractors in light fishing is limited by bright moon phase, turbid water, large waves, strong currents, and lamp power regulations. Bait attractors are expected to optimize catch and address issues with boat lift nets. This study examines the use of bait attractors along with light attractors on boat lift nets, focusing on their impact on catch yield and species composition. Conducted in May 2024 over 12 trips using experimental fishing, treatments included green mussel attractors, sardinella attractors, and no attractors (control). The total catch over 12 trips was 2,480.69 kg. Boat lift nets with green mussel attractors produced 870.88 kg (average 72.57 kg ± 44.94), with sardinella attractors 839.49 kg (average 69.96 kg ± 44.87), and without attractors 770.32 kg (average 64.19 kg ± 45.48). A total of 23 species were caught, with green mussel attractors capturing 20 species (average 7.8), sardinella attractors capturing 20 species (average 7.9), and no attractors capturing 17 species (average 7.3). The main catch to by-catch ratio was 91.82% : 8.18% (sardinella attractors), 90.26% : 9.74% (green mussel attractors), and 87.46% : 12.54% (no attractors). Results indicate bait attractors do not significantly affect catch weight compared to no bait attractors. Key words: bait attractors, boat lift nets, catch yield, composition, Jakarta bay waters